The teaching, assessment and examining of English language and literature from the Education Act of 1944 to the Education Reform Act of 1988 - Williams, Daniel Bryn (1998)
In the Preface, the focus is on the word 'standards' itself: the ineradicable human element in marking and the degree to which all marks and grades, particularly in the subject of English, are dependent upon a subjective evaluation of the quality of response - an essential component in the establishment and maintenance of standards. The various implications of the word 'standards' and the ease with with resultant ambiguities can lead the unwary commentator into wholly misleading statements are considered, and a definition is offered to serve as a touchstone for the thesis as a whole. The main body of the thesis is divided into two sections and a conclusion. Section One (containing Chapters 1-3) is largely based upon published writings about education: books, reports and papers issued by Government-appointed Committees and Councils, and officially ratified educational statistics; illustrated where appropriate by my own experience and research into the unpublished archives of Examination Boards. Section Two (containing Chapters 4-6) deals specifically with the development of GCE '0' and 'A' level examinations in English, and is very largely dependent upon my interpretation of evidence derived from examination papers, marking schemes, examiners' reports and candidates' scripts ... The Conclusion is an attempt to provide an answer to the obvious question as to why, if evidence of a widely-alleged decline in standards is as difficult to establish as the previous six chapters suggest, the charge is so widely accepted as proved. To do this it is necessary to see the matter of standards from a broader perspective than a factual focus on examination papers, candidates' scripts, examiners' reports, comparability studies and educational statistics. From the inception of the concept of a state education system there has inevitably been a political dimension to any discussion of standards, and political dimensions equally inevitably tend toward expediency and subjective reaction rather than objective assessment of perceived shortcomings. This is certainly true of the last two decades during which the political dimension has become more overt than ever before, and the gulf between political interpretation of educational achievements and that of the professionals involved has never been wider. It is the contention of the Conclusion that a key to this disparity lies in the history of the development of the National Curriculum, the nature of the political interventions therein, and the indications that these are based upon a consistent philosophy – which elevates knowledge above understanding, 'pencil-and-paper' testing above carefully weighted assessments, results above performance, and which supposes that the reintroduction of selective schools would be an automatic panacea. The Conclusion therefore looks forward beyond the stated 1988 terminal point of the study to examine the developments of the 1990s, and backward beyond the stated starting point of the 1944 Act to examine the reality of grammar school achievement. It is the final contention of this thesis that it is the fallacy and self-deception of the nostalgia for the grammar school tradition which underlies and accounts for the falsity of the claims, about declining standards.